Représentations de la mère nature: Une lecture écoféministe de la poésie de Jeanne Benguigui. Issue 3 (December 2019) - MAILLOT, MÉLANIE
Abstract : Despite the gradual rise of feminism and ecology since the 1950s, ecofeminism is a very recent concept and is seldom applied to the study of literary texts. This article provides an ecofeminist reading of the poems of Jeanne Benguigui, a French-speaking Algerian poet whose work has not yet been the subject of much literary criticism. This article reads Benguigui's poetic work through the lens of ecofeminist theory, analysing the recurring theme of nature. The aim is to analyse the literary modalities that inform this particular angle of interpretation, which is in itself a novelty in the research devoted to this poet.